PENGENALAN SUMBERDAYA LAUT DAN SUMBERDAYA MOLUSKA BAGI SISWA USIA DINI DI SEKOLAH DASAR NEGERI 2 OMA, KECAMATAN PULAU HARUKU KABUPATEN MALUKU TENGAH - Haumahu, Sara; A. Uneputty, Prulley; Kesaulya, Irma; Natan, Juliana; A. Tuapattinaja, Maureen (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2022)
People's awareness of the marine environment should be started by the student in Elementary School. The public service program was conducted to increase student knowledge of the marine environment and the fisheries resources and also to protect that. This program consists of giving a lecture, discussion, and evaluation to the student of SD Negeri 2 Oma, Haruku Island Regency, Central Maluku. The topics consist of the marine environment and the importance of this environment, types of the shore, marine mollusc resources (definition and clasification), economically important molluscs, marine Gastropoda which consumed by local people, and how to protect the marine environment and its resources. Based on the evaluation, student knowledge increased from <30% before socialization to >90% after socialization. It means that education processes for the elementary student about the problems of the marine environment and its resources increase significantly, and need more information on other marine resource.